Exosomal MicroRNAs as Mediators of Cellular Interactions Between Cancer Cells and Macrophages - Kwon, Yoojung; Kim, Misun; Kim, Youngmi; Jung, Hyun Suk; Jeoung, Dooil (Frontiers in Immunology, 2020)
Tumor microenvironment consists of cancer cells and various stromal cells such as endothelial cells, cancer-associated fibroblasts (CAFs), myeloid-derived suppressor cells (MDSCs), neutrophils, macrophages, and other innate and adaptive immune cells. Of these innate immune cells, macrophages are an extremely heterogeneous population, and display both pro-inflammatory and anti-inflammatory functions. While M1 macrophages (classically activated macrophages) display anti-tumoral and pro-inflammatory functions, M2 macrophages display pro-tumoral and anti-inflammatory functions. Cellular interactions and molecular factors in the tumor microenvironment affect the polarization of macrophages. We review molecules and immune cells that influence the polarization status of macrophages. Tumor-associated macrophages (TAMs) generally express M2 phenotype, and mediate many processes that include tumor initiation, angiogenesis, and metastasis. A high number of TAMs has been associated with the poor prognosis of cancers. MicroRNAs (miRNAs) have been known to regulate cellular interactions that involve cancer cells and macrophages. Tumor‐derived exosomes play critical roles in inducing the M1 or M2‐like polarization of macrophages. The roles of exosomal miRNAs from tumor cells in the polarization of macrophages are also discussed and the targets of these miRNAs are presented. We review the effects of exosomal miRNAs from TAMs on cancer cell invasion, growth, and anti-cancer drug resistance. The relevance of exosomal microRNAs (miRNAs) as targets for the development of anti-cancer drugs is discussed. We review recent progress in the development of miRNA therapeutics aimed at elevating or decreasing levels of miRNAs.